PERBANDINGAN SENYAWA SIANIDA PADA DAUN SINGKONG DENGAN PERENDAMAN NaHCO3 DAN Ca(OH)2 - Elfira Maya Sari; Siti Nurfajriah (Journal of Research and Education Chemistry, 2022)
Cassava contains the 80-90% carbohydrates, while Cassava leaves contain proteins, minerals, vitamins, and toxins that called Glucocide Cyanogenic. Glucose Cyanogenic can be hydrolyzed into Cyanide Acid which can bond with fe 2+ or fe 3+ in blood so that be able to degrade oxygen levels in the body cells. The purpose of this study is to know the effects of submersion NaHCO3 solution and Ca(OH)2 solution with time variations of submersion to the levels of cyanide in the cassava leaves. The pressence of Cyanide in the cassava leaves uses UV vis Spectrophotometer. The data was statistically analyzed by using a two-way anova test. According to the research, the highest levels of Cyanide found in NaHCO3 solution with 41,2656 ppm, with a reduction levels of Cyanide by 22.05% and The Ca(OH)2 with 53,9218 ppm with a reduction of Cyanide levels by 34.77% in 1 hour soaking. A statistical value of 0.106 and 0.116 (p>0.05) indicates that there is no differences of submersion of NaHCO3 solution and Ca(OH)2 solution with the time variatons that already done.